2021
DOI: 10.1055/a-1646-1151
|View full text |Cite
|
Sign up to set email alerts
|

Peroral endoscopic myotomy for management of cricopharyngeal bars (CP-POEM): a retrospective evaluation

Abstract: Background Cricopharyngeal bars (CPBs) are a unique etiology of oropharyngeal dysphagia. Symptomatic patients are managed with endoscopic dilation or surgical myotomy. Cricopharyngeal peroral endoscopic myotomy (CP-POEM) is an emerging technique for the management of dysphagia due to CPBs. This study evaluated technical success, clinical success, adverse events, and long-term recurrence following CP-POEM. Methods Consecutive patients who underwent POEM for management of CPBs between May 2015 and Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The benefit of an endoscopic approach (e.g., rigid, flexible) is that it mitigates against some of the major risks of surgery, which can include recurrent laryngeal nerve injury, fistula formation, and mediastinitis [ 11 ]. Risks from any type of myotomy have been reported to range from 0-39% [ 9 ], with the risk of open myotomy 13.6% in 1 study, compared to 7.4% in the largest C-POEM series to date [ 8 , 12 ]. Regarding outcomes, endoscopic myotomy has shown equivalent efficacy, and in 1 report better efficacy, compared to traditional open myotomy [ 9 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefit of an endoscopic approach (e.g., rigid, flexible) is that it mitigates against some of the major risks of surgery, which can include recurrent laryngeal nerve injury, fistula formation, and mediastinitis [ 11 ]. Risks from any type of myotomy have been reported to range from 0-39% [ 9 ], with the risk of open myotomy 13.6% in 1 study, compared to 7.4% in the largest C-POEM series to date [ 8 , 12 ]. Regarding outcomes, endoscopic myotomy has shown equivalent efficacy, and in 1 report better efficacy, compared to traditional open myotomy [ 9 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early data from case series are encouraging, with high technical and clinical success rates based on the resolution of symptoms [ 6 , 7 ]. The largest cohort to date is a retrospective series on 27 patients that had a technical success of 100%, clinical success of 100% over a median follow up of 42 months, and an adverse event rate of 7.4% [ 8 ]. Here, we report our experience of 5 patients undergoing C-POEM for symptomatic cricopharyngeal bar with a step-by-step video demonstration.…”
Section: Introductionmentioning
confidence: 99%
“…The largest study to date is a retrospective study including 27 patients showed a 100% technical and clinical success rate with a 7.4% of AEs (16).…”
Section: Cp-poemmentioning
confidence: 99%
“…Cricopharyngeal bar POEM (CP-POEM) allows the transection of the cricopharyngeus and a small amount of the distal esophageal muscle using principles of TSE. A retrospective study of 27 patients reported 100% clinical and technical success with mild to moderate adverse events in 7.4% of the patients [ 93 ]. It should be noted that CP-POEM can be technically challenging as the cricopharyngeus muscle is not always apparently identified endoscopically to estimate the site of mucosal entry.…”
Section: Other Third-space Endoscopic Proceduresmentioning
confidence: 99%